Assessment of interprofessional team collaboration scale (AITCS): further testing and instrument revision - Orchard, Carole; Pederson, Linda L.; Read, Emily; Mahler, Cornelia; Laschinger, Heather (The journal of continuing education in the health professions, 2018)
Introduction: The need to be able to assess collaborative practice in health care teams has been recognized in response to the direction for team-based care in a number of policy documents. The purpose of this study is to report on further refinement of such a measurement instrument, the Assessment of Interprofessional Team Collaboration Scale (AITCS) first published in 2012. To support this refinement, two objectives were set: Objective 1: to determine whether the items from the data collected in 2016 load on the same factors as found for the 2012 version of the 37-item AITCS. Objective 2: to determine whether the items in the subscales of the AITCS could be reduced while retaining psychometric properties similar to those from the earlier versions of the AITCS. - Methods: Initially, the overall data sets of 1002 respondents from two hospitals and four community agencies were analyzed for demographics and scale and subscale mean values, SDs, and mean item scores. After deletion of respondents because of missing data, 967 respondents were available for the first analysis. An exploratory factor analysis was then conducted to determine the factor structure. All respondents with any random missing data were further removed to reduce the data set to 676 responses, followed by a confirmatory factor analysis to find a model fit resulting in an item reduction in the scale. - Results: The result was a 23-item AITCS-II for practitioners that retained acceptable levels of reliability and validity within 3 subscales—partnership (8 items), cooperation (8 items), and coordination (7 items). - Discussion: The shortened version of the AITCS-II is a valid and reliable instrument that can be used to assess collaboration in health care teams in practice settings.